SYCOPHANCY AS AN OBJECT OF SCIENCE: A LITERATURE REVIEW (Journal of Philosophy Culture and Political Science, 2022)
Abstract: Sycophancy a rather complex concept. The study of sycophancy is very difficult. Because there are many synonymous concepts of sycophancy that can be based on fraud, deception, subordination and worship, loneliness, defamation, gossip and extortion. At the same time, in political science, actual problems and features of the concept of sycophancy have not been fully studied. There is sycophancy in society and no matter how we consider it insignificant, we cannot get rid of it. For these reasons, there are many statements that speak of sycophancy. Therefore, we think it is important to view sycophancy as an object of science and its literature review. The purpose of this article is to systematize the results of scientific research on the concept of sycophancy. To achieve this purpose, attention was paid to scientific publications on the concepts of «sycophancy» and «adulation» in English. These concepts helped clarify the nature of sycophancy. To solve the main problem, we conducted a content analysis of articles indexed in the Scopus database. To identify the problem, we paid special attention to 17 publications. We have noticed that there are a lot of research topics about sycophancy. We determined this using the methods of comparative, historical, structural-functional and institutional approaches used in the study. We think that these topics are studies that solve important problems in the life of society.Key words: sycophancy, synonymous concepts of sycophancy, worship, culture, power, corruption.